Mathematical analysis of cholera typhoid co-infection transmission dynamics - Matsebula, Lunga; Nyabadza, Farai (Frontiers in Applied Mathematics and Statistics, 2022)
Typhoid fever and cholera remain a huge public health problem on the African continent due to deteriorating infrastructure and declining funding for infrastructure development. The diseases are both caused by bacteria, and they are associated with poor hygiene and waste disposal systems. In this paper, we consider a nonlinear system of ordinary differential equations for the co-infection of typhoid and cholera in a homogeneously mixing population. The model's steady states are determined and analyzed in terms of the model's reproduction number. Impact analysis - how the diseases impact each other - is carried out. Numerical simulations and sensitivity analysis is also given. The results show that the control of the diseases should be carried out in tandem for the greatest impact of disease control. The results have important implications in the management of the two diseases.